2013
DOI: 10.1172/jci69884
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure homeostasis is maintained by a P311–TGF-β axis

Abstract: P311 is an 8-kDa intracellular protein that is highly conserved across species and is expressed in the nervous system as well as in vascular and visceral smooth muscle cells. P311-null (P311 -/-) mice display learning and memory defects, but alterations in their vasculature have not been previously described. Here we report that P311 -/-mice are markedly hypotensive with accompanying defects in vascular tone and VSMC contractility. Functional abnormalities in P311 -/-mice resulted from decreased total and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 44 publications
(55 reference statements)
2
44
0
1
Order By: Relevance
“…2 Although the molecular mechanism of P311 action remained unknown for years, we recently found that P311 is an RNA-binding protein that stimulates TGF-b1 to -b3 translation in vivo in the vascular smooth muscle as well as in vascular smooth muscle and NIH-3T3 cells in vitro. 1,2 Because TGF-b plays critical roles in fibrogenesis, 39 here we conducted studies to determine whether P311 may have a function in cutaneous scar formation. We found that P311 expression is up-regulated in excisional wounds compared with normal skin during the proliferative phase of healing, and it is further increased in expression during the remodeling phase, when the scar is formed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Although the molecular mechanism of P311 action remained unknown for years, we recently found that P311 is an RNA-binding protein that stimulates TGF-b1 to -b3 translation in vivo in the vascular smooth muscle as well as in vascular smooth muscle and NIH-3T3 cells in vitro. 1,2 Because TGF-b plays critical roles in fibrogenesis, 39 here we conducted studies to determine whether P311 may have a function in cutaneous scar formation. We found that P311 expression is up-regulated in excisional wounds compared with normal skin during the proliferative phase of healing, and it is further increased in expression during the remodeling phase, when the scar is formed.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) was performed at the University of Chicago Pathology Core Facility. Briefly, The IHC procedure was applied to formalin-fixed, paraffin-embedded 5-mm tissue sections, which were incubated with anti-human P311 antibody 2 (1:50 dilution) after antigen unmasking by boiling in fresh citrate buffer. The reactions were developed with Vectastain ABC kit (Vector Laboratories, Burlingame, CA).…”
Section: Ihcmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that TGF-b signaling pathway is also involved in BP homeostasis [56]. When initially synthesized, TGF-b1 is an inactive precursor polypeptide.…”
Section: Furin May Regulate Bp By Modulation Of Transforming Growth Fmentioning
confidence: 99%